2021
DOI: 10.3390/ma14164451
|View full text |Cite
|
Sign up to set email alerts
|

Computing the Fatigue Life of Cold Spray Repairs to Simulated Corrosion Damage

Abstract: This paper summarises the findings of an investigation into the durability of cold spray repairs, also known as supersonic particle deposition or SPD repairs, to simulated corrosion damage in AA7075-T7351 aluminium alloy specimens. A feature of this paper is that it is the first to show how to perform the mandatory durability analysis of repaired corroded structures, where the corroded material is first removed by machining and then repaired using cold spray, in a fashion consistent with the requirements delin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 41 publications
3
13
0
Order By: Relevance
“…A view of the failure surface is also shown in Figure 6. The fatigue surface was essentially Mode I and, as such, resembled those seen in previous papers 24,32,[39][40][41][42] for Mode I fatigue crack growth in materials that ranged from bridge steels to the highstrength aerospace quality aluminum alloys AA7075-T7351 and AA7050-T7451. As a result, as we will see in the next section, the growth of this naturally occurring crack is consistent with the exponential crack growth histories associated with the growth of naturally occurring sub millimeters cracks seen in both RAAF and USAF aircraft.…”
Section: The Fatigue Testsupporting
confidence: 80%
See 3 more Smart Citations
“…A view of the failure surface is also shown in Figure 6. The fatigue surface was essentially Mode I and, as such, resembled those seen in previous papers 24,32,[39][40][41][42] for Mode I fatigue crack growth in materials that ranged from bridge steels to the highstrength aerospace quality aluminum alloys AA7075-T7351 and AA7050-T7451. As a result, as we will see in the next section, the growth of this naturally occurring crack is consistent with the exponential crack growth histories associated with the growth of naturally occurring sub millimeters cracks seen in both RAAF and USAF aircraft.…”
Section: The Fatigue Testsupporting
confidence: 80%
“…Fortunately, as noted by Sanaei and Fatemi, 15 and also in a range of references, 1,14,16,18–34 the Hartman–Schijve crack growth equation, namely, italicda/italicdNgoodbreak=Dκp, can frequently be used to model the growth of both small and long cracks. Here, N is the number of cycles, a is the crack length/depth, and D and p are material constants.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…A new axial fatigue test specimen design was also proposed to substantiate the fatigue performance of cold spray repair on a localised cavity [17,18]. With the release of USAF Structures Bulletin EZ-19-01 and the consideration of existing military standards (MIL-STD-1530D and JSSG-2006), a few applicability studies of Hartman-Schijve crack growth for cold spray repairs showed promising correlation with experimental data for durability and damage tolerance analysis (DADTA) [19][20][21]. However, these papers were for specific components and conducted with less than eight sample sizes in controlled environments.…”
Section: Introductionmentioning
confidence: 99%